Non–steady State Modeling of the Ventilatory Depressant Effect of Remifentanil in Awake Patients Experiencing Moderate-to-severe Obstructive Sleep Apnea. (February 2019) - Doufas, Anthony G.; Shafer, Steven L.; Rashid, Nur Hashima Abdul; Kushida, Clete A.; Capasso, Robson
Editor's Perspective: What We Already Know about This Topic: Patients with obstructive sleep apnea are often said to have increased sensitivity to opioid-induced ventilatory depression What This Article Tells Us That Is New: The hypothesis that patients with moderate-to-severe obstructive sleep apnea are more sensitive to remifentanil-induced ventilatory depression was tested in 20 control patients with mild or no obstructive sleep apnea and 30 patients with moderate-to-severe obstructive sleep apnea, defined as an apnea/hypopnea index of 15 or more episodes per hour of sleep The predicted remifentanil effect site concentration at which half-maximal depression of minute ventilation occurred in awake patients receiving a remifentanil infusion of 0.2 µg · kg −1 of ideal body weight per minute did not differ between control patients and patients with moderate-to-severe obstructive sleep apnea This does not support the notion that adults with moderate-to-severe obstructive sleep apnea have increased sensitivity to opioid-induced ventilatory depression Background: Evidence suggests that obstructive sleep apnea promotes postoperative pulmonary complications by enhancing vulnerability to opioid-induced ventilatory depression. We hypothesized that patients with moderate-to-severe obstructive sleep apnea are more sensitive to remifentanil-induced ventilatory depression than controls. Methods: After institutional approval and written informed consent, patients received a brief remifentanil infusion during continuous monitoring of ventilation. We compared minute ventilation in 30 patients with moderate-to-severe obstructive sleep apnea diagnosed by polysomnography and 20 controls with no to mild obstructive sleep apnea per polysomnography. Effect site concentrations were estimated by a published pharmacologic model. We modeled minute ventilation as a function of effect site concentration and the estimated carbon dioxide. Obstructive sleep apnea status, body mass index, sex, age, use of continuous positive airway pressure, apnea/hypopnea events per hour of sleep, and minimum nocturnal oxygen saturation measured by pulse oximetry in polysomnography were tested as covariates for remifentanil effect site concentration at half-maximal depression of minute ventilation (Ce50 ) and included in the model if a threshold of 6.63 ( P < 0.01) in the reduction of objective function was reached and improved model fit. Results: Our model described the observed minute ventilation with reasonable accuracy (22% median absolute error). We estimated a remifentanil Ce50 of 2.20 ng · ml –1 (95% CI, 2.09 to 2.33). The estimated value for Ce50 was 2.1 ng · ml –1 (95% CI, 1.9 to 2.3) in patients without obstructive sleep apnea and 2.3 ng · ml –1 (95% CI, 2.2 to 2.5) in patients with obstructive sleep apnea, a statistically nonsignificant difference ( P = 0.081). None of the tested covariates demonstrated a significant effect on Ce50 . Likelihood profiling with the model including obstructive sleep apnea suggested that the effect of obstructive sleep apnea on remifentanil Ce50 was less than 5%. Conclusions: Obstructive sleep apnea status, apnea/hypopnea events per hour of sleep, or minimum nocturnal oxygen saturation measured by pulse oximetry did not influence the sensitivity to remifentanil-induced ventilatory depression in awake patients receiving a remifentanil infusion of 0.2 μg · kg –1 of ideal body weight per minute. Abstract : The hypothesis that patients with moderate-to-severe obstructive sleep apnea are more sensitive to remifentanil-induced ventilatory depression was tested in 20 control patients with mild or no obstructive sleep apnea and 30 patients with moderate-to-severe obstructive sleep apnea, defined as an apnea/hypopnea index of 15 or more episodes per hour of sleep. The predicted remifentanil effect site concentration at which half-maximal depression of minute ventilation occurred in awake patients receiving a remifentanil infusion of 0.2 mcg · kg −1 of ideal body weight per minute did not differ between control patients and patients with moderate-to-severe obstructive sleep apnea. This does not support the notion that adults with moderate-to-severe obstructive sleep apnea have increased sensitivity to opioid-induced ventilatory depression.Supplemental Digital Content is available in the text.